ANALISIS PEMBELAJARAN AKIDAH AKHLAK DALAM KURIKULUM MERDEKA DI MAN 2 SLEMAN - Rangga Iskandar Dinata; Muh Wasith Achadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Educational institutions have a very vital role in educating the nation's life. More attention has been devoted by various parties to improve the quality and quality of education, especially in educational institutions. In the life of the nation today, moral education is an important factor to be able to create a virtuous nation. Therefore, the purpose of this study is to find out more clearly and thoroughly how the role of the curriculum and educational institutions in implementing moral creed learning, especially in MAN 2 Sleman educational institutions. The research method used by researchers is qualitative research by conducting an analytical descriptive approach based on field data collection. The research was conducted at MAN 2 Sleman with the research subject being the moral creed subject teacher. The results of this study state that learning akidah akhlak at MAN 2 Sleman based on the Merdeka Belajar Curriculum has been implemented. To improve the quality of teachers in understanding the implementation of Merdeka Belajar Curriculum itself, MAN 2 Sleman always makes efforts for this. so that it can be said that the implementation of Merdeka Belajar Curriculum as the latest curriculum is running smoothly